KEKURANGAN ASUPAN BESI DAN SENG SEBAGAI FAKTOR PENYEBAB STUNTING PADA ANAK - Dyah Kusudaryati, Dewi Pertiwi (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
ABSTRACT Nutritional inputs are necessary for childrenâs growth. Deficiencies of iron and zinc are associated with growth faltering in children. Growth faltering is showed with the occurring of stunting where children have HAZ < -2 SD. Negative impact of stunting are impaired of physical, mental, cognitive and intellectual development and also low birthweight of children of women of short stature.Â Several result study show that iron or zinc suplementation among stunting children can improve in height and have positive effect on linear growth. Â Keywords : iron, zinc, stunting, growth